A 58-Year Old Male with Cognitive Deteriorations Caused by Septum Pellucidum Cyst: A Case Report - Chen, Li-Ming; Zhu, Ming-Xin; Zhang, Yu-Fen; Ma, Se-Hui; Yi, Yao; Xia, Lie-Xin; Wu, Yan; Pei, Lei (Frontiers in Aging Neuroscience, 2017)
Dementia is known to be induced by vascular dementia and certain neurodegenerative diseases. The presenting features of disordered memory, intellect and personality often result in referral to a neurologist initially. Septum pellucidum cyst (SPC) is a rare clinical finding and defined as a cystic structure between the lateral ventricles. SPC induced memory disorder and dementia has been seldom reported in which the clinical features are atypical and can be misdiagnosed. The main difficulty is to establish a correlation between symptoms and the cyst. When indicated, the treatment is essentially surgical and the ideal operative technique is also a matter of debate. Here, we reported a 58-year-male Chinese patient who presented with memory impairment one year ago. Both the physical and laboratory examinations were performed to evaluate the general conditions of the patient. Brain MRI was applied to observe SPC and the neighboring brain structures. Mini-Mental State Exam (MMSE) and Montreal Cognitive Assessment (MoCA) were used to assess cognitive function. The results of the patient’s laboratory examinations were normal. However, the patient exhibited severe sleeplessness along with cognitive deteriorations despite short-term (less than 2 weeks) use of benzodiazepines with regular dose. Magnetic resonance imaging (MRI) fulfills the consensus criteria for clinical diagnosis of SPC. Furthermore, the results of MMSE and MoCA were showed mild cognitive impairment before the treatment of SPC. After neuroendoscopic fenestration of SPC, the patient’s syndromes were disappeared, and his cognitive function was improved. In conclusion, the patient’s symptoms were due to a secondary lesion attributed to the cyst. Comprehensive clinical evaluation and MRI help diagnose SPC induced dementia.